Distribution of the main helminthosis in hens in Chechen Republic - V. H. Gadaev (Российский паразитологический журнал)
Ascaridiosis, heterakidosis and syngamosis are widely distributed in hens at floor-pasture land scheme of maintenance in Chechen Republic. 57,2; 50,5 and 38,75 % of hens are infected respectively with Ascaridia galli, Heterakis gallinarum and Syngamus trachea at intensity of infection 32,6±3,85, 32,6±3,8 and 37,6±3,4 sp.